Higher Education Challenges in the Era of COVID-19 from the Perspective of Educators and Students (Ghana, Georgia and Pakistan Cases): A Literature Review - Butakor, Paul Kwame; Kakutia, Tamar; Shah, Syed Mir Muhammad; Hunt, Elena (European Scientific Journal, ESJ, 2023)
For the last three years, the entire world has faced a colossal phenomenon due to the COVID-19 pandemic. All sectors and areas of life have been affected, which has forced rapid and radical changes towards adaptation in its wake. The unexpected pandemic’s mark and impact on education is more severe and longer lasting than imagined. It has evidently disrupted education provision at an unprecedented scale. This paper is a literature review that focuses on the experience of different countries and education systems during the COVID-19 pandemic. Based on the analysis of the existing literature and research on this issue, from the perspective of educators and students, including the experience of different countries around the world, the pandemic has had a great impact on higher education. This has resulted to digital transformation, which implies overcoming many challenges. The review uses particular examples of higher education in the era of COVID-19 in Georgia, Ghana, and Pakistan. The measures taken to continue education in spite of the pandemic are also highlighted. Although this phenomenon proved to be challenging, it has initiated enormous opportunities for creativity within progress. This paper further discussed barriers that students and academics faced during online teaching-learning, the pros and cons of online teaching-learning, the quality of teaching-learning, and the state of preparedness for future education.